Relationships between oxidative stress and sleep parameters in patients with obstructive sleep apnea syndrome. Issue 2 (2014) - Abakay, Özlem; Şen, Hadice Selimoğlu; Yüksel, Hatice; Yılmaz, Süreyya; Palanci, Yılmaz; Tanrıkulu, Abdullah Çetin; Abakay, Abdurrahman
No abstract available